2013
DOI: 10.1371/journal.pone.0074084
|View full text |Cite
|
Sign up to set email alerts
|

Image Ambiguity and Fluency

Abstract: Ambiguity is often associated with negative affective responses, and enjoying ambiguity seems restricted to only a few situations, such as experiencing art. Nevertheless, theories of judgment formation, especially the “processing fluency account”, suggest that easy-to-process (non-ambiguous) stimuli are processed faster and are therefore preferred to (ambiguous) stimuli, which are hard to process. In a series of six experiments, we investigated these contrasting approaches by manipulating fluency (presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 96 publications
(127 reference statements)
6
63
1
Order By: Relevance
“…Our study aimed to evaluate the impact of object-and subject-related cognitive challenge on eye movements during perception of contemporary art by expert and naive viewers. In line with previous research (Belke et al, 2015;Jakesch & Leder, 2009;Jakesch et al, 2013;Muth et al, 2015), the degree of ambiguity and complexity in images was positively linked with appreciation, suggesting that despite its effortful processing, this kind of challenging art can be liked. However, this pattern was not replicated for the third component of subject-related cognitive challenge as no relation between perceived inconsistency and liking was found.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study aimed to evaluate the impact of object-and subject-related cognitive challenge on eye movements during perception of contemporary art by expert and naive viewers. In line with previous research (Belke et al, 2015;Jakesch & Leder, 2009;Jakesch et al, 2013;Muth et al, 2015), the degree of ambiguity and complexity in images was positively linked with appreciation, suggesting that despite its effortful processing, this kind of challenging art can be liked. However, this pattern was not replicated for the third component of subject-related cognitive challenge as no relation between perceived inconsistency and liking was found.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we also took into account the subject-related cognitive challenge, that is, the subjective reactions evoked by an artwork. Amongst various estimates of cognitive challenge studied in empirical aesthetics (Jakesch & Leder, 2009;Jakesch et al, 2013;Muth & Carbon, 2013;Muth et al, 2015), we chose to focus on perceived inconsistency, complexity, and ambiguity, as these measures allowed us to capture different aspects of cognitive challenge in contemporary art. Whereas "ambiguity" is often associated with multiple meanings and interpretations that could be attributed to the stimuli (Muth et al, 2015), "complexity" usually refers to more formal aspects, such as variety of elements and ways they are organized (Nadal, Munar, Marty, & Cela-Conde, 2010).…”
Section: Subjective Evaluations Of Artworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous, behavioral studies, we repeatedly found that ambiguous paintings were liked more than non-ambiguous paintings (Jakesch et al, 2013; Jakesch and Leder, 2015). However, although we used the same stimuli, we found no main effect for liking in the current study.…”
Section: Discussionmentioning
confidence: 83%